Estudo comparativo entre a realidade de Belém-PA e Cidades de Brasília-DF e Santa Maria-RS, quanto a durabilidade de fachadas, sob à ação do calor, choque térmico e chuva dirigida - NERI, Tonio Márcio (2023)
This work deals mainly with a review of the scientific academic production on the analysis of the performance of facades, exposed to climate actions, located in 03 different Brazilian bioclimatic zones. This comparative study consists of verifying the levels of exposure and the agents of degradation corresponding to each of these regions, as well as the analysis of the materials that make up these facades. The work was carried out based on bibliographical research, which obtained a result of 32 related articles, however, only 07 articles were similar to the theme. As a result of the research, it was identified among the cities of Belém -PA, Brasília -DF and Santa Maria -RS, the most critical zone (Z2) and the mildest (Z8), regarding the degree of exposure and appearance of degradation agents, in which they act as markers for mapping possible building pathologies.